Test Methods for Qualitative and Quantitative Determination of the Polymer Content Present in Modified Asphalt Binders - Salazar Delgado, Jorge (2025)
Costa Rica, as many countries, are implementing the use of polymer-modified asphalts for road construction, the growing market offers several types of polymers that improve the rheological properties of asphalts, significantly. The most common polymers are SBR, SBS, tire rubber in powder, EMA and EVA among others. The modifiers percentages are between 1% to 5 % m/m of the asphalt binder. However, little research has been conducted for quantifying the amount of polymer incorporated into the asphalt binder. Accordingly, the methods to determine qualitatively or quantitatively the presence of polymers present in the asphalt are the objective of this. This article is aimed to asphalt binder’s laboratories, mainly, but also to engineers and professionals working on road construction and Quality Assurance.